Growth and yield response of carrot (Daucus carota l.) to different rates of soil amendments and spacing (Journal of Science and Technology, 2016)
A 5 x 2 factorial field experiment in a randomised complete block design with four replications was conducted at the College of Agriculture Education, University of Education, Winneba, Mampong Campus to investigate the growth and yield responses of carrot to different rates of soil amendments and spacing. The five rates of soil amendments were: (i) 10 t/ha chicken manure (ii) 15 t/ha chicken manure (iii) 20 t/ha chicken manure (iv) 300 kg/ha NPK (15-15-15) and (v) Control (no soil amendment). The two spacings were: (i) 30 cm x 5 cm and (ii) 20 cm x 5 cm. The application of 15 t/ha and 20 t/ha decomposed chicken manure improved vegetative growth, increased root yield and gave more income. More plants were however, infected by Sclerotium rolfsii by the application of the 20t/ha chicken manure. Soil amendment rates did not suppress nematode populations but the highest root galling index was recorded on the control plants. The wider spacing of 30cm x 5cm promoted vegetative growth and increased root length of carrot but planting at closer spacing of 20cm x 5cm resulted in higher total and marketable yields and also increased income and profit.